2015
DOI: 10.1515/helmin-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Research Note. Pearsonema plica and Eucoleus böhmi infections and associated lesions in wolves (Canis lupus) from Italy

Abstract: SummaryReports of Pearsonema plica and Eucoleus böhmi infections in wolves (Canis lupus) in Europe are limited and data on associated lesions are lacking. In the present study urinary bladders, nasal turbinates and faecal samples from 8 necropsied wolves were examined for P. plica and E. böhmi infections and associated lesions. P. plica was identifi ed in the bladder of four wolves. At histological examination, follicular chronic cystitis and eosinophilic cystitis were found. E. böhmi nematodes and eggs were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…However, a third urinary capillariid species, namely Capillaria travassoi, has been reported in domestic felids in North America, but it is still not clear whether P. feliscati and C. travassoi should be considered distinct species or the same species [3]. Adults of these capillariids reside in the urinary bladder and, more rarely, in the ureters and renal pelvis of domestic and wild carnivores, in which they may be responsible for urinary capillariosis [4][5][6][7][8]. The host spectrum of P. plica includes wild and domestic canids and felids, while P. feliscati only infects felids [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, a third urinary capillariid species, namely Capillaria travassoi, has been reported in domestic felids in North America, but it is still not clear whether P. feliscati and C. travassoi should be considered distinct species or the same species [3]. Adults of these capillariids reside in the urinary bladder and, more rarely, in the ureters and renal pelvis of domestic and wild carnivores, in which they may be responsible for urinary capillariosis [4][5][6][7][8]. The host spectrum of P. plica includes wild and domestic canids and felids, while P. feliscati only infects felids [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…P. plica is most often reported in dogs with access to outdoor environments, especially hunting dogs and kenneled dogs (Senior et al, 1980;Callegari et al, 2010). The red fox (Vulpes vulpes) is considered the wild reservoir of P. plica for domestic animals in Europe (Davidson et al, 2006;Magi et al, 2014), but the wolf (Canis lupus) is emerging as an additional reservoir (Bagrade et al, 2009;Mariacher et al, 2015). Despite the high prevalence in the red fox, urinary capillariosis has been rarely reported in dogs in Italy (Callegari et al, 2010;Maurelli et al, 2014) and the real occurrence of the disease is probably underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, especially in case of P. plica heavy parasite burdens, the infection has been accounted for urinary clinical signs and bladder lesions, both in domestic carnivores ( Senior et al, 1980 ; Callegari et al, 2010 ; Rossi et al, 2011 ) and in wild canids. Lesions associated with P. plica infection generally consist of eosinophilic or lymphocytic infiltration of urinary bladder, kidney and ureters in foxes ( Fernandez-Aguilar et al, 2010 ; Bork-Mimm and Rinder, 2011 ; Alić et al, 2015 ), while follicular chronic cystitis has been reported in wolves ( Mariacher et al, 2015 ). In the bear of the present case, only scattered hyperemic foci in the bladder mucosa and mild cystitis were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, foxes ( Vulpes vulpes ) and wolves ( Canis lupus ) are regarded as the reservoir hosts of P. plica ( Bagrade et al, 2009 ; Bork-Mimm and Rinder, 2011 ; Magi et al, 2014 ; Mariacher et al, 2015 ). Likely, the populations of red fox and wolf that live in the same area of the bear ( Di Sabatino et al, 2014 ) may have contributed to environmental contamination with P. plica eggs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation